Benchmark Prices and Iraqi Oil Prices: The Asymmetric Effects of Benchmark Prices on Three Iraqi Oil Blends - Volkan Kahraman; Nukhet Dogan; Hakan Berument (International Journal of Energy Economics and Policy, 2024)
This paper examines the asymmetric effects of benchmark oil prices on the prices of the three major Iraqi oil blends (Basrah Light, Basrah Heavy and Kirkuk) using Kilian and Vigfusson's (2011) non-linear VAR specification. The empirical evidence reveals that a decrease in benchmark prices decreases Basrah Light and Kirkuk oil blends more than an increase in the benchmark increases the prices of these two Iraqi blends for the October 2002-October 2019 period. However, the asymmetric behavior of Basrah Heavy is the reverse for the April 2015-October 2019 period. Moreover, as the magnitude of the benchmark oil price shocks increases, the degree of asymmetry increases. This shows that Iraq cannot benefit from oil price increases and market developments for its two most important export blends: Basrah Light and Kirkuk.